Bronchial schwannoma: a singular lesion as a cause of obstructive pneumonia. (19th October 2016) - Oliveira, Rui Caetano; Nogueira, Tiago; Sousa, Vítor; Carvalho, Lina
Abstract : Bronchial schwannomas are very rare pulmonary lesions, but its awareness is important to reach correct diagnosis and decide proper intervention. Clinical and radiological characteristics are mainly unspecific and pathological examination usually provides the definite diagnosis. In small lesions, endoscopic approach may be sufficient, but in large lesions associated with organising pneumonia surgical intervention may be required. Prognosis is typically favourable. We describe a case of a woman, aged 66 years, with productive cough and sporadic haemoptysis, dyspnoea, anorexia, excessive sweating and weight loss with 2 months evolution. CT scan showed a soft tissue dense lesion on the left hilum with 3.75 cm with 18-Fludeoxyglucose uptake. Left upper lobectomy was performed. Gross examination revealed a polypoid mass without necrosis, histologically showing cellular dense (Antoni A) and less dense (Antoni B) areas with Verocay bodies, slightly pleomorphic spindle cells, without mitotic activity and positive for S100 protein on immunohistochemistry.